2022
DOI: 10.47766/jetlee.v2i1.204
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Poster Media to Enhance Student Learning Outcomes in Descriptive Text Writing

Abstract: This research reported observations regarding students' learning activities. The results of the study revealed that most students did not enjoy the learning process and yet become passive learners. This can be driven by several aspects, particularly the employment of conventional methods by teachers during the class, and the media exploited was not engaging. Thus, this study proposed a resolution to construct learning activities more engaged. This study suggested that the application of poster media can be an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…In the writing test, this group of students achieved a 5.953-point increase in average post-test scores compared to the pre-test. Previous studies have shown that posters are better than essays for improving writing skills, both because it is easier to create a persuasive text with them (Salih, 2021) and because it is more easy to give feedback to their students (Cetin & Eymur, 2017) or because posters as a means of learning become more active than other and motive to students for writing (Jannah et al, 2022). In another scenario, it has been reported that though many students complain because they have to design a poster, they also have read more for their presentation and this motivates them because they learned more (Kinikin & Hench, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the writing test, this group of students achieved a 5.953-point increase in average post-test scores compared to the pre-test. Previous studies have shown that posters are better than essays for improving writing skills, both because it is easier to create a persuasive text with them (Salih, 2021) and because it is more easy to give feedback to their students (Cetin & Eymur, 2017) or because posters as a means of learning become more active than other and motive to students for writing (Jannah et al, 2022). In another scenario, it has been reported that though many students complain because they have to design a poster, they also have read more for their presentation and this motivates them because they learned more (Kinikin & Hench, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Talking about organizational performance is also inseparable from organizational communication. Prawiro Suntoro interprets performance is a result achieved by a group or organization within a certain time through effective communication (Fadillah, 2014;Jannah et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%